2003
DOI: 10.1093/emboj/cdg036
|View full text |Cite
|
Sign up to set email alerts
|

A conserved tyrosine in the neck of a fungal kinesin regulates the catalytic motor core

Abstract: The neck domain of fungal conventional kinesins displays characteristic properties which are re¯ected in a speci®c sequence pattern. The exchange of the strictly conserved Tyr 362, not present in animals, into Lys, Cys or Phe leads to a failure to dimerize. The destabilizing effect is con®rmed by a lower coiled-coil propensity of mutant peptides. Whereas the Phe substitution has only a structural effect, the Lys and Cys replacements lead to dramatic kinetic changes. The steady state ATPase is 4-to 7-fold accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…The microtubule-induced mant-ADP release was measured by mixing mant-ADP charged kinesin and microtubules in the presence of unlabeled ATP, either manually in a spectrophotometer (Aminco-Bowman AB2) or in a stopped-flow instrument (Biologics SF-3) under conditions published before (29).…”
Section: Methodsmentioning
confidence: 99%
“…The microtubule-induced mant-ADP release was measured by mixing mant-ADP charged kinesin and microtubules in the presence of unlabeled ATP, either manually in a spectrophotometer (Aminco-Bowman AB2) or in a stopped-flow instrument (Biologics SF-3) under conditions published before (29).…”
Section: Methodsmentioning
confidence: 99%
“…One conspicuous residue is tyrosine Y362 in the center of the neck coiled-coil domain. We showed that it is required for proper folding of the ␣-helical coiled-coil, but also for down-regulation of the motor activity, presumably in the inactivated, cargo-free state (Schafer et al, 2003). To explain how this residue inhibits the motor activity under repressing conditions, but allows full function under activating conditions, we hypothesized that the neck can switch between an ␣-helical coiled-coil conformation (active) and another, unknown conformation that allows interaction between Y362 and the core motor domain (inactivated).…”
Section: Introductionmentioning
confidence: 91%
“…To introduce cross-links between the neck domains of the two polypeptide chains of a kinesin dimer, proline 342 was exchanged to cysteine, because this residue is expected to be in the first a-position of the ␣-helical neck coiled-coil (Schafer et al, 2003). Such an arrangement is known to form interstrand disulfide bonds readily (Zhou et al, 1993).…”
Section: Cloning Of Constructsmentioning
confidence: 99%
See 2 more Smart Citations